The Dance of Shiva : Fourteen Indian Essays - Coomaraswamy, Ananda K., (Brill | Manohar Publishers & Distributors, 2023)
The Dance of Shiva by Coomaraswamy explores the metaphysical part of India. It explains India's contribution to the entire humanity. This book addresses the Indian ethos in a more detailed manner since Indian philosophy is often misinterpreted by the Westerners. Topics associated with fine arts, philosophy, and music are covered in this book; these include the Hindu and Buddhist perception of art from the aesthetical and historical points of view. Popular sculptures such as Nataraja, another incarnation of Shiva, represented as the God of dance, and multiple-armed images in Indian art are studied extensively. There is also a section on Indian music, which is also studied in great detail. Besides, this volume also covers the issue of the status of Indian women, Sahaja philosophy, the intellectual community, Indian youth, and individualism.